Neglected, yet significant role of FOXP1 in T-cell quiescence, differentiation and exhaustion - Kaminskiy, Yaroslav; Kuznetsova, Varvara; Kudriaeva, Anna; Zmievskaya, Ekaterina; Bulatov, Emil (Frontiers in Immunology, 2022)
FOXP1 is ubiquitously expressed in the human body and is implicated in both physiological and pathological processes including cancer. However, despite its importance the role of FOXP1 in T-cells has not been extensively studied. Although relatively few phenotypic and mechanistic details are available, FOXP1 role in T-cell quiescence and differentiation of CD4+ subsets has recently been established. FOXP1 prevents spontaneous T-cell activation, preserves memory potential, and regulates the development of follicular helper and regulatory T-cells. Moreover, there is growing evidence that FOXP1 also regulates T-cell exhaustion. Altogether this makes FOXP1 a crucial and highly undervalued regulator of T-cell homeostasis. In this review, we discuss the biology of FOXP1 with a focus on discoveries made in T-cells in recent years.